Opini Publik di Media Sosial: Analisis Isi Opini Kandidat Ahok-Djarot dan Anies-Sandi di Twitter - Dini Nur Asih; Muhamad Rosit (CoverAge: Journal of Strategic Communication, 2018)
Social networking sites are considered an important channel for expressing opinions and actively participating in political life. Jakarta 2017 election into the spotlight when Basuki Tjahja Purnama or Ahok allegedly defamed the religion of Islam. In the first round, Agus-Sylvi pair must accept defeat and the couple Ahok-Djarot and Anies-Sandi go to the second round of 2017 Regional Head Election of Jakarta. On April 12, 2017, KPUD DKI Jakarta held the last debate discussing the problems and the exposure of work program which has been diserausn by both candidates based on the hashtag #DebatPilkadaDKI. The purpose of this study is to know the direction of opinion Ahok-Djarot candidates and Anies-Passwords on the hashtag #DebatPilkadaDKI as well as the process of forming public opinion. This research uses three concepts are public opinion, social media twitter, and candidate debate. The paradigm used is positivism, quantitative research, descriptive research type, unit analysis using thematic analysis unit (pro, contra, and neutral categorization), variable definition is public opinion variable and social media twitter, analysis model is content analysis, opinion and social media twitter, population and sample that is random sampling, data collecting technique that is documentation, research instrument is sheet coding, data analysis technique using formula percentage, and validity and reliability of data using inter-coder reliability. The results of this study indicate that the pair Ahok-Djarot opinion direction in the last debate tend to be positive than the couple Anies-Sandi.